Bilateral breast cancer: a case study. Issue 3 (15th September 2020) - Tudu, Rajanigandha; Kumar, Anup; Singh, Rashmi; Raina, Payal
Abstract: Background: Breast cancer is the most common cancer among females worldwide. Increasing breast cancer incidence rates, improved diagnosis and management modalities and growing life expectancy have resulted in increasing numbers of women at risk of developing contralateral primary breast cancer. Bilateral breast cancer can occur synchronously or metachronously. Material and methods: This study reports three cases of bilateral breast cancer patients treated at our oncology department between March 2018 and March 2019. The features of presentation, investigation, diagnosis and follow-up care are the highlights of this study. Results: Bilateral breast cancer was noted in three patients among the study population in the age group of 35 –55 years. Two of these patients had metachronous bilateral breast cancer, and one patient developed cancer in the second breast during the course of management. The second breast cancers differed histologically from primary breast cancer. Conclusion: Poor awareness on breast cancer care and the lack of national screening guidelines and programmes, and poor infrastructure, all contribute to late presentation and difficult breast cancer management. Proper history, clinical examination and imaging of opposite breast should be done to ensure adequate and timely management of bilateral breast cancer.